COLLABORATIVE GOVERNANCE DALAM PEMBERDAYAAN PELAKU USAHA MIKRO EKMIRA MELALUI FASILITASI PENDAFTARAN MEREK DAGANG - Dwi Febrianti; Hayat; Hirshi Anadza (Halu Oleo University, 2025)
This research aims to understand, describe and analyse the implementation of collaborative governance in empowering Ekmira micro-enterpreneurs actors through actors through trademark registration facilitation. The research method used is qualitative, as the researcher can conduct direct observations in the field to see the prevailing situations and conditions. The results of this research are that the implementation of collaborative governance in empowering Ekmira micro businesses through facilitating trademark registration has been implemented quite well. However, several obstacles prevent the collaboration from facilitating the program from functioning optimally. This can be seen from the indicators that are met and the constrains that require improvement in achieving successful collaborative governance according to Goldsmith and Kettl (2009) as cited in Kurniadi (2020), which include networked structure, commitment to a common purpose, trust among the participants, governance, acces to authority, distributive accountability/responsibility, information sharing, and acces to resources.